Farmakokinetik dan Ketersediaan Hayati Relatif Sediaan Kapsul, Tablet Salut Enterik dan Supositoria Ketoprofen - Yeyet C. Sumirtapura; Badruzzaman Saungnage; Mamat Rachmat (Institut Teknologi Bandung, 2002)
Pharmacokinetics and relative bioavailability of ketoprofen in capsule, enteric coated tablet and suppository, following si ngle dose administration (50 mg for capsule and tablet, and 100 mg for suppository), had been studied in six healthy Indonesian volunteers with three-way crossover design. The drug concentrations in the plasma samples were assayed by a TLC -densitometric method. The results showed that ketoprofen was rapidly absorbed from the gastro-intestinal tract after administration of capsule with peak plasma concentration of about 3.7 mg/ml, which was reached in about one hour following the drug administration. Mean peak plasma concentrations of about 4.3 and 4.6 mg/ml were attained in relatively delayed time, i.e. about 2 and 1.5 hours, respectively after administration of enteric coated tablet and suppository. Ketoprofen was eliminated rapidly from the body with an el imination half-life of about 2.5 hours. The highest absorption efficiency was showed by the enteric coated tablet, followed by the capsule and the suppository.